1999
DOI: 10.1007/bf02347223
|View full text |Cite
|
Sign up to set email alerts
|

Cesium, strontium, europium(III) and plutonium(IV) complexes with humic acid in solution and on montmorillonite surface

Abstract: The effect of Aldrich humic acid (HA) on the mobility of ~37Cs, 85Sr, ~SZEu and 239pu radionuclides was studied in Ca-montmorillonite suspensions. Verified 2-sites-2-species (2s2s) models correspond to an intensive interaction of all elements with humificated surface, what is in a remarkable contrast with the weak complexation of cesium and even strontium in solutions -the neutral ligand interaction constants 13 (1/mol) are log 13<-9.9 and 7.56+0.21 for Cs and Sr, respectively. The result for europium complexa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Owing to the high alpha activity of Am(III) and Cm(III) the number of such studies on their sorption by mineral oxides is limited [10,11]. Instead, extensive studies have been carried out using lanthanides as analogue of trivalent actinides [12][13][14][15][16]. The mechanism of the sorption process of metal ions by the mineral oxides is explained in terms of the surface complexation models [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the high alpha activity of Am(III) and Cm(III) the number of such studies on their sorption by mineral oxides is limited [10,11]. Instead, extensive studies have been carried out using lanthanides as analogue of trivalent actinides [12][13][14][15][16]. The mechanism of the sorption process of metal ions by the mineral oxides is explained in terms of the surface complexation models [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In forest soils, both soluble and insoluble plutonium compounds remain in top layers (Bunzl 1998;Druteikienė 1999;Lujanienė 2002). The main reason of plutonium compounds retention in organic soil horizons are associations between humic substances and Pu ions (Fujikawa 1999;Macášek 1999;Sokolik 2003). It was found that besides organic matter Pu was also bound with Fe/Mn oxides (e.g., Komosa 2002).…”
Section: Introductionmentioning
confidence: 98%
“…Though organic soil horizons do not contain enough clay minerals to immobilize cesium, many authors (Beli et al 1994;Takenaka et al 1998;Nakamaru et al 2007;El Samad et al 2007;El-Reefy et al 2006;Zhiyanski et al 2008;Wacławek et al 2004;Dołhańczuk-Śródka et al 2006aDołhańczuk-Śródka et al , 2006bDołhańczuk-Śródka et al , 2006c reported the highest 137 Cs activities just in upper horizons, rich in organic matter. A reason of Cs + retention in organic horizons could be explained by formation of certain complexes between cesium ions and humic acids (Macášek 1999). There is a hypothesis which suggested that organic matter modifies the adsorption properties of clay minerals in soil (El-Reefy 2006).…”
Section: Introductionmentioning
confidence: 99%
“…An increase in the molecular weight and a release of CO 2 were found when HAs from soil and peat in aqueous media were irradiated with g-rays in the dose range 10-100 kGy [8]. The effect of HS on the g-irradiated pollutants, herbicides and pesticides was extensively studied [1,10,11]. The secondary electromagnetic ultraweak radiation-radiochemiluminescence (RCL)-following g-radiolysis of the HA-alkaline solution was detected recently.…”
Section: Introductionmentioning
confidence: 99%